A-Stable Time Discretizations Preserve Maximal Parabolic Regularity - Kovács, Balázs; Li, Buyang; Lubich, Christian (SIAM Journal on Numerical Analysis)
Keywords: Numerical Analysis; Applied Mathematics; Computational Mathematics

Numerical analysis of parabolic problems with dynamic boundary conditions - Kovács, Balázs; Lubich, Christian (IMA Journal of Numerical Analysis)
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Asymptotic spectral gap and Weyl law for Ruelle resonances of open partially expanding maps - ARNOLDI, JEAN FRANCOIS; FAURE, FRÉDÉRIC; Weich, Tobias (Ergodic Theory and Dynamical Systems)
We consider a simple model of an open partially expanding map. Its trapped set ${\mathcal{K}}$ in phase space is a fractal set. We first show that there is a well-defined discrete spectrum of Ruelle resonances which describes the asymptotic of correlation functions for large time and which is parametrized by the Fourier component $\unicode[STIX]{x1D708}$ in the neutral direction of the dynamics. We introduce a specific hypothesis on the dynamics that we call ‘minimal captivity’. This hypothesis is stable under perturbations and means that the dynamics is univalued in a neighborhood of ${\mathcal{K}}$ . Under this hypothesis we show the existence of an asymptotic spectral gap and a fractal Weyl law for the upper bound of density of Ruelle resonances in the semiclassical limit $\unicode[STIX]{x1D708}→ ∞$ . Some numerical computations with the truncated Gauss map and Bowen–Series maps illustrate these results.
Keywords: Applied Mathematics; General Mathematics

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Convolution algebras for Heckman–Opdam polynomials derived from compact Grassmannians - Rösler, Margit; Remling, Heiko (Journal of Approximation Theory)
Keywords: Applied Mathematics; General Mathematics; Numerical Analysis; Analysis

Robust Preconditioning Estimates for Convection-Dominated Elliptic Problems via a Streamline Poincaré--Friedrichs Inequality - Axelsson, Owe; Karátson, János; Kovács, Balázs (SIAM Journal on Numerical Analysis)
Keywords: Numerical Analysis; Applied Mathematics; Computational Mathematics

On the numerical performance of a sharp a posteriori error estimator for some nonlinear elliptic problems - Kovács, Balázs (Applications of Mathematics)
Keywords: Applied Mathematics

Influence of Triphenyl Phosphate on Degradation Kinetics of Ultrahigh-molecular-weight Polyethylene in Inert and Oxidative Media - Korobeinichev, Oleg P.; Paletsky, Alexander A.; Gonchikzhapov, Munko B.; Shundrina, Inna K.; Chen, Haixiang; Liu, Naian (Procedia Engineering)
Keywords: Applied Mathematics

Combustion Chemistry and Decomposition Kinetics of Forest Fuels - Korobeinichev, Oleg P.; Paletsky, Alexander A.; Gonchikzhapov, Munko B.; Shundrina, Inna K.; Chen, Haixiang; Liu, Naian (Procedia Engineering)
Keywords: Applied Mathematics

A normal form for definite quadratic forms over $\mathbb{F}_{q}[t]$ - Kirschmer, Markus (Mathematics of Computation)
An efficient algorithm to compute automorphism groups and isometries of definite Fq[t]-lattices for odd q is presented. The algorithm requires several square root computations in Fq₂ but no enumeration of orbits having more than eight elements.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Parameter Identification of Constitutive Models for Fluidsaturated Porous Media within an FE-Setting - Mahnken, Rolf; Steinmann, P. (ZAMM - Journal of Applied Mathematics and Mechanics / Zeitschrift für Angewandte Mathematik und Mechanik)
Keywords: Applied Mathematics; Computational Mechanics

Numerical Simulation of Interface Debonding during Fibre Pull-Out Tests - Döbert, C.; Mahnken, Rolf; Stein, E. (ZAMM - Journal of Applied Mathematics and Mechanics / Zeitschrift für Angewandte Mathematik und Mechanik)
Keywords: Applied Mathematics; Computational Mechanics

Improvements for finite-element implementation of the Gurson Model - Mahnken, Rolf (ZAMM - Journal of Applied Mathematics and Mechanics / Zeitschrift für Angewandte Mathematik und Mechanik)
Keywords: Applied Mathematics; Computational Mechanics

Modular symbols for reductive groups and p-adic Rankin–Selberg convolutions over number fields - Januszewski, Fabian (Journal für die reine und angewandte Mathematik (Crelles Journal))
Keywords: Applied Mathematics; General Mathematics

A Newton-Multigrid algrithm for elasto-plastic/viscoplastic problems - Mahnken, Rolf (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

SU(d)-Biinvariant Random Walks on SL(d,C) and their Euclidean Counterparts - Rösler, Margit; Voit, Michael (Acta Applicandae Mathematicae)
Keywords: Applied Mathematics

Counting nilpotent Galois extensions - Klüners, Jürgen; Malle, G. (Journal für die reine und angewandte Mathematik (Crelles Journal))
We obtain strong information on the asymptotic behaviour of the counting function for nilpotent Galois extensions with bounded discriminant of arbitrary number fields. This extends previous investigations for the case of abelian groups. In particular, the result confirms a conjecture by the second author on this function for arbitrary groups in the nilpotent case. We further prove compatibility of the conjecture with taking wreath products with the cyclic group of order 2 and give examples in degree up to 8.
Keywords: Applied Mathematics; General Mathematics

An inverse finite-element algorithm for parameter identification of thermoelastic damage models - Mahnken, Rolf (International Journal for Numerical Methods in Engineering)
Keywords: Applied Mathematics; General Engineering; Numerical Analysis

A stabilization procedure by line-search computation for first order approximation strategies in structural optimization - Mahnken, Rolf; Stein, E.; Bischoff, D. (International Journal for Numerical Methods in Engineering)
Keywords: Applied Mathematics; General Engineering; Numerical Analysis

Adaptive time-step control in creep analysis - Mahnken, Rolf; Stein, Erwin (International Journal for Numerical Methods in Engineering)
Keywords: Applied Mathematics; General Engineering; Numerical Analysis